Quality of buckwheat-enriched wheat bread and its antihyperlipidemic effect in statin treated patients. Issue 1 (September 2015) - Stokić, Edita; Mandić, Anamarija; Sakač, Marijana; Mišan, Aleksandra; Pestorić, Mladenka; Šimurina, Olivera; Jambrec, Dubravka; Jovanov, Pavle; Nedeljković, Nataša; Milovanović, Ivan; Sedej, Ivana
Abstract The buckwheat-enriched wheat bread was produced by the substitution of wheat flour with the wholegrain buckwheat flour at the level of 50%. Hydrothermal treatment of wholegrain buckwheat flour prior to the bread production resulted in a product with better sensory quality than the wheat bread, which was confirmed by the consumer test. The preference test showed that 71.88% of the consumers gave the advantage to the buckwheat-enriched wheat bread. Futhermore, its nutritional quality and antioxidant capacity was significantly improved in comparison with the wheat bread (2.22 times higher total dietary fibre and 4.29 times higher total phenolics content). In order to examine whether changes in dietary components can have beneficial effects on certain markers of atherosclerosis, antihyperlipidemic efficiency of the buckwheat-enriched wheat bread was tested in normal weight patients on statin therapy over one-month dietetic intervention. Significant decrease in total cholesterol and LDL-cholesterol, as well as the ratio of LDL/HDL cholesterol was obtained.